Effect of chemical treatments and additives on properties of chicken feathers thermoplastic biocomposites. (November 2018) - Casadesús, M; Macanás, J; Colom, X; Cañavate, J; Álvarez, MD; Garrido, N; Molins, G; Carrillo, F
The valorisation of chicken feathers waste was researched in this work through the preparation of composites using ground chicken feathers as a filler (20% vol/vol) and polypropylene or low-density polyethylene matrices. In order to improve the compatibility between chicken feathers and the matrices, two different strategies were followed: first, by the chemical modification of the chicken feathers by either acetylation or silanization and second, by the addition of adhesion promoters like maleated polypropylene and maleated polyethylene. The effect of those treatments on the physical, mechanical and structural properties of the thermoplastic-chicken feathers biocomposites, which are mainly related to the fibre–matrix compatibility, was analysed. Results show that the addition of 20% (vol/vol) of unmodified chicken feathers to the thermoplastic matrices results in a significant decrease of the tensile strength associated to a weak interfacial adhesion as it was demonstrated by scanning electron microscopy. However, when the adhesion promoters were added to the mixture, a significant increase in the tensile strength was noticed, particularly when the composites were obtained by a process at 180℃. On the contrary, acetylation and silane treatments of the chicken feathers did not result in any practical improvement of the macroscopic properties of the biocomposites.